Incongruity between scientific knowledge and ordinary perceptions of nature: an ontological perspective for forest hydrology in Japan. Issue 2 (4th March 2017) - Komatsu, Hikaru; Rappleye, Jeremy
ABSTRACT: There exists a significant incongruity between scientific knowledge and ordinary perceptions concerning the relation between forest and water (e.g. droughts and floods). Traditionally, forest hydrologists interpreted this incongruity using the deficit model, i.e. this incongruity is viewed as one that must be overcome through efforts to disseminate scientific knowledge more widely across society. However, one previous study suggested an alternative interpretation for the incongruity observed in Japan: the incongruity is induced by an enduring conflict between modern science and indigenous culture, one which purportedly promotes an "emotional" outlook to nature. This review attempts to clarify this alternative interpretation by utilizing a diverse range of disciplinary perspectives. We first clarify, using psychology and philosophy, that the "emotional" outlook of Japanese is rooted in a notion of self which is interdependent. Reviewing historical studies, we then find that the interdependent self was replaced by the notion of the independent self in the West in the Middle Ages. Since modern science was born out of this historical context in the seventeenth and eighteenth centuries, modern science assumes the same grammar of thought, i.e. begins with the notion of an independent self. We finally reveal that contemporary forest hydrology also has reproduced this grammar. We thus conclude that this difference in ontological grammar between contemporary forest hydrology and that of the ordinary public in Japan is a major cause for the incongruity between scientific knowledge and ordinary perceptions there. From this novel ontological perspective, we envision an alternative future of forest hydrology in Japan.